Anuran community in a neotropical natural ecotone - Matavelli, Rodrigo [UNESP]; Campos, Aldenise Martins; Santos, Clarenice Loiola; de Andrade, Gilda Vasconcellos (My University, 2019)
Little attention has been given to natural ecotone areas around the world. However, natural ecotones play an important role in sustaining high species richness and a unique biodiversity that do not exist in the adjacent ecosystems. We present the first anuran fauna inventory in a natural ecotone between Cerrado and restinga in northeastern Maranhão State, Brazil. The survey was conducted at 24 sampling points in an area of 14,360 km2. We sampled anurans during the rainy season (January to July 2010) using the visual search (youth and adults) and acoustic search (male reproductive activity of vocalization) methods simultaneously to detect the presence of adult individuals. We recorded 50 anuran species belonging to 15 genera and five families. The anuran fauna showed high species richness, which may be explained by the fact that the study area is a natural biogeographic transition zone.
Keywords: Amphibians; Conservation efforts; Inventory; Maranhão; Transition areas